Different Aspects of Head and Neck Squamous Cell Carcinoma: Cancer Stem Cells, their Niche and Targeted Therapy - Küçükgüven, Meriç Bilgiç; Çelebi-Saltik, Betül (Current Stem Cell Research & Therapy, 2021)
Head and Neck Squamous Cell Carcinoma (HNSCC) is categorized as the sixth most common cancer worldwide, with an incidence of more than 830,000 cases per year and a mortality rate of 50%. Tobacco use, alcohol consumption, and Human Papillomavirus infection are the prominent risks for HNSCC. Despite significant developments in the treatment of HNSCC, a high rate of recurrences makes the clinical situation worse and results in poor survival rates. Recent perspectives demonstrate that although epithelial transformation plays a crucial role in cancer development, tumor surrounding microenvironment takes part in the progression of cancer as well. Cancer Stem Cells (CSCs), which harbor unlimited self-renewal capacity, have a crucial role in the growth of HNSCC and this cell population is responsible for tumor recurrence unless eliminated by targeted therapy. CSCs are not only a promising target for tumor therapy but also a crucial biomarker to determine the patients at high risk for undetermined results and disease development, just as the bone marrow, which is the niche of hematopoietic and mesenchymal stem cells, is important for stem cell maintenance. Similarly, the concept of microenvironment is also important for the maintenance of CSCs. Apart from the cell-cell interactions, there are many parameters in the cancer microenvironment that affect the development of cancer, such as extracellular regulation, vascularization, microbial flora, pH, and oxygenation. The purpose of this review is to introduce HNSCC, explain the role of CSCs and their microenvironment, and refer to the conventional and novel targeted therapy for HNSCC and CSCs.
Keywords: head and neck squamous cell carcinoma